THE INFLUENCE OF PERCEIVED ORGANIZATIONAL SUPPORT, JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT TOWARD ORGANIZATIONAL CITIZENSHIP BEHAVIOR (A Study of the Permanent Lecturers at University of Lambung Mangkurat, Banjarmasin) - Meiske Claudia (Faculty of Economics and Business, Universitas Gadjah Mada, 2018)
The population in this research is all of the permanent lecturers employed at University of Lambung Mangkurat (ULM). The respondents are taken from 4 academic ranks, which are represented by Asisten Ahli (Instructor), Lektor (Assistant Professor), Lektor Kepala (Associate Professor), and Guru Besar (Professor). One hundred and thirty samples were collected by using a proportional-stratified random sampling method. A Partial Least Square (PLS) method was used to analyze the data. The results showed that lecturers with a positive perception of the organizational support available to them feel more satisfied with their job, which in turn encourages the creation of a high organizational commitment and results in the emergence of positive organizational citizenship behavior (OCB). These study’s results showed us the application of social exchange theory and organizational support theory in a higher educational institution. The findings of this study are considered to be important, as they provide additional empirical evidence regarding the importance of organizational support as a basis for improving the ULM lecturers' job satisfaction, organizational commitment, and OCB. The implications and further research are also discussed.